H/D Exchange for 4-Aminopyridine: Application on MAO in Sera of Multiple Sclerosis Patients (Medico Legal Update, 2021)
Multiple sclerosis (MS) is a neurological disorder characterized by a complex array of symptoms affectingmovement and the senses. It is an inflammatory disease of the central nervous system (CNS) causes an injuryin the myelin sheaths, leading to demyelination and thus, consequently, a series of neurologically dysfunctionknown as relapses. 4-Aminopyridine is used in the treatment of MS patients as a selective voltage blockerchannel. The study designed over two stages, first 4-aminopyridine went under H/D exchange, and thenboth deuterated and non-deuterated 4-AP was applied on the serum of MS patients and the activity of serummonoamine oxidase was estimated. The study included 120 subject which divided over two groups, controland MS patients, each of which contain 60 subject. The activity of MAO was significantly (P